METODE PEMBELAJARAN MATA PELAJARAN ALQURAN HADIS PADA MAN 2 BUKITTINGGI - Yopi M; A. Rahman Ritonga; Deswalantri Deswalantri (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2019)
The background of this study is based on the author's interest in examining further the methods used by teachers on the Qur'anic Hadith subjects in class XI GPA at MAN 2 Bukittinggi. Students do not feel bored and excited in learning because teachers use methods that are not monotonous. The type of research I use is field research with a qualitative approach. The key informants in this study were teachers of the Qur'anic Hadith subject, and supporting informants in this study were students of class XI majoring in GPA. Data collection techniques that the authors use are observation, interviews, and documentation. Then the data obtained from the informants were analyzed using qualitative descriptive methods. The results of this study indicate that the learning method of the Koran used by the teachers of the Koran subjects in class XI GPA can be concluded that the teacher mostly uses the lecture method, but interspersed with other purposes, such as discussion methods, questions and answers, and different ways.